Association between heavy metals exposure and infertility among American women aged 20–44 years: A cross-sectional analysis from 2013 to 2018 NHANES data - Lin, Jie; Lin, Xiaoyan; Qiu, Jiahui; You, Xiumi; Xu, Jinbang (Frontiers in Public Health, 2023)
Background: Infertility has been confirmed as a significant medical and social problem. Heavy metal exposure refers to a risk factor for infertility, which is capable of damaging the reproductive system of males and females. However, heavy metal exposure and female infertility have rarely been investigated. The aim of this study was to analyze the association between heavy metal exposure and female infertility. Methods: A cross-sectional study using data from three cycles of the National Health and Nutrition Examination Survey (NHANES, 2013-2018) was performed. Female infertility was evaluated by positive responses to question rhq074 in the questionnaire. Cadmium (Cd), lead (Pb), mercury (Hg), and arsenic (As) levels in blood or urine were examined by inductively coupled plasma mass spectrometry. The correlation between heavy metal and female infertility was analyzed through weighted logistic regression. Results: A total of 838 American women aged 20-44 years were covered in the study. Urinary Cd and urinary As levels were significantly higher in infertile women than in control women (P < 0.05, P < 0.05). Urinary As showed a positive correlation with the prevalence of female infertility, and the risk of infertility rose with the increase of urinary As levels (P for trend = 0.045). Urinary Cd was associated with female infertility in some weighted logistic regression, and urinary As (OR=1.02, 95% CI 1.00, 1.03) were positively correlated with the risk of infertility in women aged 35-44 years. The blood Pb (OR=1.67, 95% CI 1.16, 2.40, 2.49) and urinary Pb (OR=1.54, 95% CI 1.00, 2.38) in women with BMI ≥25 were positively correlated with the risk of infertility. Conclusions: Urinary As was significantly associated with female infertility, and the risk of infertility increased with higher urinary As levels. To some extent, urinary Cd was correlated with infertility. Blood/urine Pb was related to infertility in advanced age and overweight/obese women. The results of this study need to be further validated in future prospective studies.